(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
A sample of 200 participants (male = 108 and female = 92)was selected for the present study. Allthe participants were diagnosed migraine patients. The sample was selected from the civil andprivate hospitals/clinics of Rohtak, Bhiwani, Hisar and Sirsa districts ofHaryana. For the second phase of thestudy 60 patients were randomly assigned in three groups. Only those patientshaving at least two attacks in a fortnight period and scored three or more on afive point scale of perceived intensity of pain were selected for theintervention part of the study. All these 60 patients were randomly selectedfor the psychological intervention. Here, 20 patients were given Relaxationtraining alternatively for fifteen days and 20 patients were givenEMG-biofeedback therapy in the same way. One control group of 20 patients wasalso selected to which no psychological intervention was given. All these 60patients were taking medications during psychological interventions and therewere about equal number of male and female patients in each group.